1995
DOI: 10.1254/jjp.69.357
|View full text |Cite
|
Sign up to set email alerts
|

Novel Benzodioxan Derivative, 5-{3-[((2S)-1,4-Benzodioxan-2-ylmethyl)amino]propoxy}-l,3-benzodioxole HC1 (MKC-242), with a Highly Potent and Selective Agonist Activity at Rat Central Serotonin1A Receptors

Abstract: ABSTRACT-The present study characterizes the neurochemical profile of the newly synthesized compound 5-{3-[((2S)-1,4-benzodioxan-2-ylmethyl)amino]propoxy}-1,3-benzodioxole HC1 (MKC-242). In in vitro experiments, MKC-242 had high affinity for serotonin,A (5-HTIA) receptors (K;: 0.35 nM) and moderate affinity for a,-adrenoceptors (K,: 21 nM), whereas it had no appreciable affinity for any other neurotransmitter recognition sites studied and 5-HT transporter. MKC-242 (0.3-3.0 mg/kg, s.c.; 1-10 mg/kg, p.o.) caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…The net effect of diminished cell firing (and consequently diminished 5-HT release) and functional postsynaptic receptor antagonism is a reduction in serotonergic tone to the SCN. The same is true for MKC-242, although this compound may display greater agonist properties in the agonistpartial agonist-antagonist continuum (Matsuda et al, 1995). Interestingly, both compounds also share the ability to block alpha-1 adrenergic receptors; at the level of the raphe nuclei, this action too can reduce cell firing by removing excitatory noradrengic tone (Baraban and Aghajanian, 1980).…”
Section: Discussionmentioning
confidence: 93%
“…The net effect of diminished cell firing (and consequently diminished 5-HT release) and functional postsynaptic receptor antagonism is a reduction in serotonergic tone to the SCN. The same is true for MKC-242, although this compound may display greater agonist properties in the agonistpartial agonist-antagonist continuum (Matsuda et al, 1995). Interestingly, both compounds also share the ability to block alpha-1 adrenergic receptors; at the level of the raphe nuclei, this action too can reduce cell firing by removing excitatory noradrengic tone (Baraban and Aghajanian, 1980).…”
Section: Discussionmentioning
confidence: 93%
“…Isolation rearing-induced aggression has been proposed to be useful as an animal model for assessing benzodiazepine and non-benzodiazepine anxiolytic activities. We have found that the selective 5-HT 1A receptor agonist osemozotan (previously called as MKC-242) (3,15) as well as the g-aminobutyric acid A (GABA A )-receptor agonist diazepam reduced isolation-induced aggressive behavior (16,17). The antiaggressive effect of osemozotan was observed at low doses, suggesting the involvement of presynaptic 5-HT 1A receptor activation (6).…”
Section: Aggressive Behaviorsmentioning
confidence: 99%
“…Evidence has accumulated to indicate that the 5-HT 2A -and 5-HT 1A -receptor activation in the hypothalamus mediate the hyperthermic and hypothermic action, respectively, in rats (8,9). This raises the hypothesis that puerarin acts through a 5-HT 2A -and / or 5-HT 1A -receptor mechanism to exert its thermal effect.…”
Section: Introductionmentioning
confidence: 99%